Qualidade e vida de prateleira de patê elaborado com subprodutos comestíveis do abate de ovinos. - Amaral, Deborah Silva do (2012)
Many edible meat by-products, produced from the lamb slaughter, are often wasted, although they represent excellent sources of many nutrients. The preparation of pâté may be an alternative to the use of this raw material, and contribute to the development of lamb sector by the offer of new products to the consumer market. The objective of this work was to produce and evaluate the quality and shelf life of a lamb pâté, made with the blood, liver and trimmed meat, packed in glass and polyamide casing, stored at 4±1 °C for 90 days. The formulation of the product was composed by 12% meat, 25% liver, 13% blood, 20% water and 30% fat, as well as spices and herbs. The lamb pâté was prepared in accordance with the requirements in the Brazilian legislation, regarding chemical and microbiological parameters, being able to use. It presented high iron content (9.0 mg/100g), important in the control of anemia. The levels of essential amino acids, found in 100g of the lamb pâté, exceeded the recommended daily allowances for adults, especially leucine, valine and histidine. The lamb pâté showed also a significant percentage of linoleic acid (16.68%), which is essential to the human body. The lamb pâté had good acceptability, whereas 55.6 % of the panelists indicated that they will probably buy it. The storage period showed good microbiological stability, but its shelf life was limited by the regression of the acceptability of sensory attributes, especially, overall impression and texture. The physico-chemical parameters of lamb pâté were affected by storage time, especially the instrumental texture, which indicated instability of emulsion during storage, and an increase in hardness, springiness and gumminess. Difference between the two packages used to the lamb pâté was detected only to the moisture, TBARS, hardness and gumminess parameters; however, there was no change in the microbiological and sensory quality of the product, this result highlights the advantages of the packages studied. In fact, this study suggests that the development of lamb pâté is a viable alternative to add value to the edible byproducts of lamb in order to obtain a product with high nutritional value.